Oracle application express for mobile web applications - Hartman, Roel (Expert's voice in Oracle., 2013)
Oracle Application Express for Mobile Web Applications is an action driven book, taking you by the hand through all required steps in building your very own web application that will run on phones, tablets, and other mobile devices. Because you've built every piece of it yourself, you will know exactly how every tiny part is used and how you can tweak it to your own - or your customer's - taste. Oracle Application Express is widely known in the Oracle community as a great tool for creating web applications suitable for desktop browsers. Features have now been added to open up the world of mobile browsing, bringing the simplicity and expressiveness of Appliction Express to bear in developing applications to run with an almost-native look and feel on platforms such as iOS, Android, and Windows Phone. Oracle Application Express for Mobile Web Applications helps you translate your knowledge of Oracle Application Express into developing for mobile devices. The book and its running example provide all the knowledge you need to create professional looking mobile web applications. Takes you through building a mobile web application from start to finish. Gives insight into the components necessary for a professional looking mobile application. Helps you become an even better and more all-round Oracle Application Express developer.